The Influence of Film and Storage on the Phenolic and Antioxidant Properties of Red Raspberries (Rubus idaeus L.) cv. Erika - Angelo Maria Giuffrè; Lamia Louadj; Paola Rizzo; Emanuela De Salvo; Vincenzo Sicari (MDPI AG, 2019)
In this paper, the effect of the packaging material and storage method on red raspberries produced at Reggio Calabria (Italy) was studied. For this purpose, the fruits were stored immediately after harvest in different conditions: in the fridge at 1 °C and in the freezer at −20 °C, using different packaging materials, two new patented films (nanoactive A) and (nanoactive B), one common packaging film (polyethylene terephthalate), and other fruits were left without any packaging material. Chemical parameters were analysed at harvest to have the initial characteristics without any conditioned storage and to distinguish the post-harvest effect on the fruits, then daily for storage in the fridge and monthly for storage in the freezer. The aims of our project were first to determine the qualitative characterization of these red raspberries, the optimization of their shelf-life during time in the fridge or freezer, using the different types of packaging materials and finally to highlight the usefulness of the new patented packaging materials. Nanoactive A film showed the best shelf-life in the fridge, and after 14 days the values, given as mg/100 g fresh weight, were: total phenolics (166.70), monomeric anthocyanin content (50.82), flavonoids (24.64), ascorbic acid (32.42), and 1, 1-diphenyl-2-picrylhydrazyl (DPPH) assay (95.93).